Encapsulation of poly(m-aminobenzodioxol)-Fe3O4 superparamagnetic nanorods and iron (III) thiocyanate complex in hydrogel toward hybrid solar cells. Issue 4 (August 2021) - Ferrag, Celia; Noroozifar, Meissam; Modarresi-Alam, Ali Reza; Kerman, Kagan
Abstract: In this proof-of-concept study, a nanocomposite of poly(m-aminobenzodioxol) with Fe3 O4 magnetic nanorods (PABD- Fe3 O4 NRs) was synthesized using a one-pot synthesis. The nanocomposite was characterized using transmission electron microscopy (TEM), environmental scanning electron microscopy (ESEM), and Fourier-transform infrared spectroscopy (FT-IR), which all displayed successful synthesis. The PABD- Fe3 O4 NRs were then incorporated within a graphite-implanted polyacrylamide (PAA-G) hydrogel matrix to develop an innovative nanocomposite-polymer solar cell. The additional Fe 3+ was then used to form a metal thiocyanate complex, [FeSCN] 2+, within the pores of the hydrogel. To the best of our knowledge, this study is the first to report the use of a conductive hydrogel nanocomposite for the encapsulation of the active layer within a hybrid solar cell. The incorporation of this material as a single layer enabled storage of the [FeSCN] 2+ solution as well as increased the formation of interconnected channels for faster electron transfer and diminished charge transfer resistance, and therefore, significantly enhanced the overall efficiency of the solar cell. Under simulated solar irradiation, the final FTO│TiO2 / PAA-G-PABD-Fe3 O4 NRs gel [FeSCN] 2+ │Al solar cell demonstrated a power conversion efficiency (PCE or η) of 6.08% and a significant enhancement of 2100% in comparison with the solar cells fabricated with PABD-Fe3 O4 NRs in the absence of the PAA-G and [FeSCN] 2+ complex. Our preliminary results exhibited high thermal stability and displayed superior photovoltaic properties when compared to other similar solar cells in literature. We envisage that the synthesis of hydrogel nanocomposites using various nanomaterials will significantly enhance the development of high-efficiency hybrid solar cells. Graphical Abstract: ga1